Institutional basis of management and evaluation of Ukrainian defense lands - Garazhа Y. (Land Management, Cadastre and Land Monitoring, 2017)
The management and evaluation of defense land was revealed in the article. Specific institution is the military institutе in the institutional framework for defense land. A special regime and zoning, evaluation, payment and exclusion conditions were established for these lands. The market economy has changed the land-property relations in the country. Lands for defense used only in the framework that established the state. Recently there was a tendency of land release this subcategory. This has led to their misuse, belonging to other owners. The research problem consists of the setting clear boundaries of defense land and legal regulation mechanisms of land relations. Public ownership rights applies only to the defense lands. They are located only in the state ownership. The subject is the state that implements ownership (right to possess, use and dispose of the lands of Defense). It ensures the defense of the country and territory for military sites, airfields, parts, ammunition depots. Functional use of defense land is divided into public (military schools), socio-cultural (health centers, recreation centers), industrial (military and industrial objects), residential (cantonment), commercial (commissary), special (military installations), transport ( carpark, bridges), engineering (antennas, radars), storage (defense deport). The land for military unit were given for permanent use with the justification of the project design documentation sizes. The military part of the land for permanent use with the justification sizes by the project design documentation. Safety, security and other areas are created around military and other defense installations. There are restricted areas, prohibited areas. They have a special regime. Reform of the Armed Forces of Ukraine, the State Special Transport Service leads to the release of land and real estate. Reform of the Armed Forces of Ukraine, the State Special Transport Service leads to the release of land and real estate. Military depots with fuel for rockets and other types of substances, military training grounds are dangerous both for people and for the ecological situation of the environment. If in the future they will not be used for their intended purpose, they should be brought to its original state. This land is advisable to assign a recovery mode, which provides clearing from dangerous objects and substances. After these steps, you can change their intended purpose. These funds come from the alienation of the State budget exclusively for defense purposes. Land alienated at land auctions. Contractor of land sales is determined on a competitive basis. He receives from the CMU authority to the exclusion of military property. He must have a license to conduct land auctions. He must conclude the two treaties: the first - with the organizer about their carrying out, and the second - with the Ministry of Defence (in terms of the implementation of real military equipment of objects). Lot consists of a land plot together with the objects located on it immovable military property. Keywords: institute of defence land, normative monetary evaluation, land taxation, management, regime.